Genetic Variation in KCNQ1 Associates With Fasting Glucose and β-Cell Function: A Study of 3,734 Subjects Comprising Three Ethnicities Living in Singapore - TAN, Jonathan T; NURBAYA, Siti; GARDENER, Daphne; YE, Sandra; TAI, E. Shyong; NG, Daniel P. K (Diabetes (New York, N.Y.), 2009)
The potassium voltage-gated channel, KQT-like subfamily, member 1 (KCNQ1) has been found through a genome-wide association study to be a strong candidate for conferring susceptibility to type 2 diabetes in East Asian and European populations. Our objective was to describe the association between polymorphisms at the KCNQ1 locus with insulin resistance, beta-cell function, and other type 2 diabetes-related traits in a sample of Chinese, Malays, and Asian Indians living in Singapore. We examined the associations between four previously reported KCNQ1 single-nucleotide polymorphisms (SNPs) with type 2 diabetes-related traits in 3,734 participants from the population-based 1998 Singapore National Health Survey cohort (2,520 Chinese, 693 Malay, and 521 Asian Indians). Insulin resistance was calculated from fasting insulin and glucose using the homeostasis model assessment method, whereas pancreatic beta-cell function was assessed using the corrected insulin response at 120 min (CIR(120)). SNPs rs2237897, rs2237892, and rs2283228 were significantly associated with type 2 diabetes (odds ratio [OR] 1.48, P = 3 x 10(-4); OR 1.38, P = 0.002; OR 1.31, P = 0.012, respectively). Within the Chinese population, the risk alleles for rs2237897, rs2237892, and rs2283228 were significantly associated with higher fasting glucose levels (P = 0.014, 0.011, and 0.034, respectively) and reduced CIR(120)(P = 0.007, 0.013, and 0.014, respectively). A similar trend was observed among the Malay and Asian Indian minority groups, although this did not reach statistical significance because of limited sample sizes. The increased risk for type 2 diabetes associated with KCNQ1 is likely to be caused by a reduction in insulin secretion. Further studies will be useful to replicate these findings and to fully delineate the role of KCNQ1 and its related pathways in disease pathogenesis.